MPI‐CDG from a hepatic perspective: Report of two Egyptian cases and review of literature. Issue 1 (7th September 2020) - Abdel Ghaffar, Tawhida Y.; Ng, Bobby G.; Elsayed, Solaf M.; El Naghi, Suzan; Helmy, Sarah; Mohammed, Nermine; El Hennawy, Ahmed; Freeze, Hudson H.
Abstract: MPI‐CDG is a rare congenital disorder of glycosylation (CDG) which presents with hepato‐gastrointestinal symptoms and hypoglycemia. We report on hepatic evaluation of two pediatric patients who presented to us with gastrointestinal symptoms. Analysis of carbohydrate deficient transferrin (CDT) showed a Type 1 pattern and molecular analysis confirmed the diagnosis of MPI‐CDG. Oral mannose therapy was markedly effective in one patient but was only partially effective in the other who showed progressive portal hypertension.